Akun @anitaintan dan Visualisasi Hadis: Studi Resepsi Konten di YouTube Shorts - Masruroh, Alfika Inayatul; Muttaqin, Sopian Kamil (Journal of Hadith Studies, 2024)
This study investigates the reception of Hadiths through YouTube shorts, a feature that facilitates short-form video content, appealing particularly to younger audiences and allowing for easier message absorption. The research is grounded in the rapid development of digital media, which significantly affects the transmission and reception of religious messages, especially Hadith. Two main questions are addressed: (1) What are the forms of Hadith reception and audience responses on the YouTube shorts account @anitaintan? (2) What is the sentiment toward Hadith-related content on this account? This qualitative study employs field and library research methods. Primary data were collected by identifying Hadith content on @anitaintan, selected based on upload frequency and subscriber count. Secondary data includes relevant literature and Hadith texts. Data were gathered through documentation, including screenshots and analysis of comments from uploaded videos. The analysis utilizes Marshall McLuhan’s new media theory and Ahmad Rafiq’s Hadith reception framework. McLuhan emphasizes the influence of the medium on message reception, while Rafiq classifies Hadith reception into exegetical, aesthetic, and functional types. The findings indicate that the shift from textual to visual Hadith presentation allows for greater flexibility in reception. The content creator’s engaging style enhances message delivery, making Hadith more accessible. Positive responses dominated all five videos analyzed, with negative comments appearing in only two, and neutral responses exceeding negative ones. These results suggest that digital platforms like YouTube shorts provide a contemporary space for Hadith dissemination, enabling broader engagement, especially among younger viewers.